2018
DOI: 10.1177/1545968318810810
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses and Perceived Exertion During Robot-Assisted and Body Weight–Supported Gait After Stroke

Abstract: Supplementary material for this article is available on the Neurore-habilitation & Neural Repair website along with the online version of the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
3
12
0
Order By: Relevance
“…Similar to work of Lefeber, et al [26] the effects of BWS yielded noted differences in VO 2 and cardiorespiratory demand. These authors found that in ambulatory stroke survivors, metabolic markers of exertion during robot assisted gait were less than over ground walking when in BWS walking [26].…”
Section: Measures and Proceduressupporting
confidence: 76%
See 1 more Smart Citation
“…Similar to work of Lefeber, et al [26] the effects of BWS yielded noted differences in VO 2 and cardiorespiratory demand. These authors found that in ambulatory stroke survivors, metabolic markers of exertion during robot assisted gait were less than over ground walking when in BWS walking [26].…”
Section: Measures and Proceduressupporting
confidence: 76%
“…Similar to work of Lefeber, et al [26] the effects of BWS yielded noted differences in VO 2 and cardiorespiratory demand. These authors found that in ambulatory stroke survivors, metabolic markers of exertion during robot assisted gait were less than over ground walking when in BWS walking [26]. However, during BWS minimum thresholds of exercise demand were reached, and therefore complement our findings that BWS exercise can reach intensities sufficient to challenge the cardiopulmonary system to promote gainful adaptation.…”
Section: Measures and Proceduressupporting
confidence: 76%
“…In conclusion, we cannot add any useful information on the aerobic capacity of RAGT or on the physiological response to this intervention, even though it has been reported how RAGT is less energy-consuming and cardiorespiratory stressful than overground walking training. 30,31 In future trials, it will be useful considering the intensity of the training as a factor potentially influencing the outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The walking interventions in the aforementioned studies by Klassen et al and Hornby et al were purposefully delivered at moderate to high cardiovascular intensities, which may have been a key factor in driving positive outcomes [ 56 , 57 ]. Research has shown that patients participating in robotic-assisted gait training achieve only low-intensity aerobic thresholds, relative to overground walking practice [ 58 , 59 ]; thus, participants in our study most likely did not achieve the moderate- to high-intensity guideline suggested for locomotor training. An important caveat of these studies showing association between aerobic intensity or stepping amount and improved walking outcomes investigated patients requiring minimal or no assistance to walk.…”
Section: Discussionmentioning
confidence: 89%